Recent Advances in Mechanical Vibration Energy Harvesters Based on Triboelectric Nanogenerators - Du, Taili; Dong, Fangyang; Xi, Ziyue; Zhu, Meixian; Zou, Yongjiu; Sun, Peiting; Xu, Minyi (Small (Weinheim an der Bergstrasse, Germany), 2023)
With the development of autonomous/smart technologies and the Internet of Things (IoT), tremendous wireless sensor nodes (WSNs) are of great importance to realize intelligent mechanical engineering, which is significant in the industrial and social fields. However, current power supply methods, cable and battery for instance, face challenges such as layout difficulties, high cost, short life, and environmental pollution. Meanwhile, vibration is ubiquitous in machinery, vehicles, structures, etc., but has been regarded as an unwanted by‐product and wasted in most cases. Therefore, it is crucial to harvest mechanical vibration energy to achieve in situ power supply for these WSNs. As a recent energy conversion technology, triboelectric nanogenerator (TENG) is particularly good at harvesting such broadband, weak, and irregular mechanical energy, which provides a feasible scheme for the power supply of WSNs. In this review, recent achievements of mechanical vibration energy harvesting (VEH) related to mechanical engineering based on TENG are systematically reviewed from the perspective of contact–separation (C‐S) and freestanding modes. Finally, existing challenges and forthcoming development orientation of the VEH based on TENG are discussed in depth, which will be conducive to the future development of intelligent mechanical engineering in the era of IoT. This work systematically reviews latest achievement in VEH based on TENG in the fields of mechanical engineering. The future development of VEH based on TENG is prospected and challenged.